Parliament and the supreme court: institutional conflict for supermacy of power - Sharma, Sadhna (Delhi, 1986)
The concept of the supremacy of the constitution has manifested itself in a unique dimension in the institutional conflict for supremacy of power between the two main pillars of the Indian Polity the Parliament and the Supreme Court. This study attempts to discuss in some. depth and seeks to determine the extent, the degree and the respective positions of the Parliament and the Superme Court which are interlocked in a struggle not only in their power-balance but also for supremacy in the exercise of their respective powers and positions in regard to which both hold strongly to their own different, if not opposite, view points and positions. This situation which has a far reaching conse quences for the Indian Polity as also for the Indian people has attracted the serious attention of academicians, jurists, journalists and politicians in addition to generating quite a serious and pervasive countrywide debate on this vitally important question. This book deals with this question in the light of relevant and important cases, debates in the Parliament, decisions of the Supreme Court and their resultant action and reaction of both the institutions and the effect of this institutional conflict for supremacy of power on the constitution of India.
Keywords: Supreme courtIndia